A Plea to Reassess the Role of United States Medical Licensing Examination Step 1 Scores in Residency Selection. (January 2016) - Prober, Charles G.; Kolars, Joseph C.; First, Lewis R.; Melnick, Donald E.
Abstract : The three-step United States Medical Licensing Examination (USMLE) was developed by the National Board of Medical Examiners and the Federation of State Medical Boards to provide medical licensing authorities a uniform evaluation system on which to base licensure. The test results appear to be a good measure of content knowledge and a reasonable predictor of performance on subsequent in-training and certification exams. Nonetheless, it is disconcerting that the test preoccupies so much of students' attention with attendant substantial costs (in time and money) and mental and emotional anguish. There is an increasingly pervasive practice of using the USMLE score, especially the Step 1 component, to screen applicants for residency. This is despite the fact that the test was not designed to be a primary determinant of the likelihood of success in residency. Further, relying on Step 1 scores to filter large numbers of applications has unintended consequences for students and undergraduate medical education curricula. There are many other factors likely to be equally or more predictable of performance during residency. The authors strongly recommend a move away from using test scores alone in the applicant screening process and toward a more holistic evaluation of the skills, attributes, and behaviors sought in future health care providers. They urge more rigorous study of the characteristics of students that predict success in residency, better assessment tools for competencies beyond those assessed by Step 1 that are relevant to success, and nationally comparable measures from those assessments that are easy to interpret and apply.